Design and evaluation of high power density brushless DC permanent magnet machines - Othman, Md Nazri Bin (2012)
Permanent Magnet brushless DC motors are now competing with many other types of motors in the world industries application. However, for low and medium power applications, brushless DC motors are often the main option due to its recognized advantage such as having no commutator, more efficient, need less maintenance, smaller in size and can operate at higher speeds than conventional motors. The overall objective of this project is to produce an improved prototype BLDC motor with concentrated winding concept for an aircraft actuator application. Specifically, the aim is to extract the maximum power density and torque per kilograms by utilizing high switching frequencies, high pole numbers and minimizing magnetic material content.